The Impact of VAT Rate Increases, Tax Literacy, and Financial Literacy on Potential Value Added Tax Revenue - Rani, Wahyu Mustika (IJBAMS: International Journal of Business Accounting Management Social Science, 2025)
This study aims to examine the effect of the increase Value Added Tax (VAT) rates, tax literacy, and financial literacy on potential VAT reveue. This study uses a quantitative approach with primary data obtained through the distribution of questionnaires to 101 Micro, Small, and Medium Enterprises (MSMEs) in Kalisongo Village, Malang Regency. The sampling technique was purposive using the Slovin formula. Data analysis was performed using multiple linear regression using IBM SPSS Statistic 26 software. The results show that the increase in VAT rates and financial literacy have a significant effect on potential VAT revenue. However, tax literacy does not have a significant effect partially.Simultaneously, these three variabels have a significant effect on potential VAT revenue. This finding demonstrates the importance of improving financial literacy and evaluating VAT rate policies in efforts to optimize state revenue